Epistemological approach in social research for the production of scientific theories - Doubront Guerrero, Luis Gerardo (2021)
The study aims to elucidate the epistemological approach in social research for the production of scientific theories, taking into account the conceptual weaknesses in the training of researchers that recurrently are reduced between a quantitative or qualitative approach as the guiding axis of the investigative process. The methodology used was framed in a qualitative approach, using the hermeneutical-critical method that allowed interpreting the information in units of analysis through documentary sources. In this sense, the research findings highlighted the importance of knowing the researcher’s perception of social reality, the relationship between the researcher and what is being investigated to access scientific knowledge and the investigator’s procedural strategy to respond to the objectives of the study. In conclusion, quantitative or qualitative methodological approaches are the result derived from an entire ontological, epistemological and methodological process that guides the research, acquiring relevance only procedurally.